Risk Factors for Feline Otitis in Madiun: A Prospective Study - Khasana, Uswatun; Meles, Dewa Ketut; Praja, Ratih Novita; Tyasningsih, Wiwiek; Wibawati, Prima Ayu (Universitas Airlangga, 2023)
This study aimed to determine the risk factors in cats associated with the incidence of otitis. A total of 169 cat samples were evaluated by filling out questionnaires and interviewing owners, then an examination was carried out to determine symptoms and treatment so that appropriate action could be taken. Data were analyzed descriptively and tested using Chi-Square analysis. As a result, there were 26 (15,4%) cats diagnosed with otitis. The results of the analysis of significant risk factors include bathing frequency, ear hygiene, and maintenance patterns that can increase the incidence of otitis. The most common clinical symptoms are pruritus, head shaking and accompanied by earwax. The description of the statement about otitis concluded that as many as 70 cat owners, most of them did not understand otitis.